Diferentes lâminas de irrigação e doses de nitrato de potássio, aplicadas via fertirrigação, sobre a cultura do mamão formosa - Santos, Francisco Sildemberny Souza dos (2006)
The present work had as objective evaluates the effect of different levels irrigation and of the application of the increasing quantity of potassium fertilization. The fertilizer used was the potassium nitrate. Crop studied was papaya, group Formosa, variety Tainung Nº 1. Research was carried at the Distrito de Irrigação Jaguaribe Apodi (DIJA), located in Limoeiro do Norte, Ceará, Brazil. In both experiments, the crop was irrigated with a drip irrigation system. Each plant had three emitters with outflow standard of 4 L h-1 and pressure of service of 10 m. Analyzed attributes were: diameter of the stem, length of fruit, average weight of the fruit, number of fruits per plant, productivity and total soluble solids levels in the fruit. In the first experiment, that deals with the irrigation depths, were applied five irrigation levels correspondent to 50, 75, 100, 125 and 150% of the Class A Pan evaporation. A randomized block design with three repetitions and five treatments was used. The results demonstrate that the utilization of greater irrigation depths increases the number of fruits per plant and productivity. However, it does not modify the diameter of the stem, length of fruit, and total soluble solids levels in the fruit. In the second experiment, referring to the potassium fertilization, the treatments had consisted of the application of four different amounts of potassium nitrate. A randomized block design, with three repetition and four treatments was used. At the end of the experiment 69, 137, 172 and 206 kg KNO3 ha-1 month-1 had been applied according to the four treatments. The use for the producer of bigger dosages of potassium nitrate increases the number of fruits for plant, the average weight of the fruits and the productivity until a certain boundary-value, from which the value of these variable starts to decrease. The application of bigger doses of the fertilizer increases the average length of the fruit. However, it does not modify the total levels soluble solids in the fruit.